A Conceptual Model of Dual-Mode Tomography Technique for Dental Diagnostics - Nur Syafiqah Amirah Ab Sukor; Juliza Jamaludin; Normaliza Ab Malik; Fatinah Mohd Rahalim; Nur Rasyiqah Mohd Fauzi; Farah Aina Jamal (Malaysian Society for Computed Tomography & Imaging Technology, 2024)
Non-Index Publication